Specializing when it counts: comparing the dose-time effect of distance variety between swimming and track running - Born, D.-P.; Ruiz-Navarro, J. J.; Lorentzen, J.; Björklund, G. (Sports, 2024)
Objective: To conduct a longitudinal retrospective analysis, explore the relationship between success at peak performance age and the number of different race distances athletes competed in each year (within-sport distance variety), and compare the dose-time effect of this distance variety throughout the development process between male swimmers and track runners.